Polygenic Heterogeneity Across Obsessive-Compulsive Disorder Subgroups Defined by a Comorbid Diagnosis - Strom, Nora I.; Grove, Jakob; Meier, Sandra M.; Bækvad-Hansen, Marie; Becker Nissen, Judith; Damm Als, Thomas; Halvorsen, Matthew; Nordentoft, Merete; Mortensen, Preben B.; Hougaard, David M.; Werge, Thomas; Mors, Ole; et al. (Frontiers in Genetics, 2021)
Among patients with obsessive-compulsive disorder (OCD), 65-85% manifest another psychiatric disorder concomitantly or at some other time point during their life. OCD is highly heritable, as are many of its comorbidities. A possible genetic heterogeneity of OCD in relation to its comorbid conditions, however, has not yet been exhaustively explored. We used a framework of different approaches to study the genetic relationship of OCD with three commonly observed comorbidities, namely major depressive disorder (MDD), attention-deficit hyperactivity disorder (ADHD), and autism spectrum disorder (ASD). First, using publicly available summary statistics from large-scale genome-wide association studies, we compared genetic correlation patterns for OCD, MDD, ADHD, and ASD with 861 somatic and mental health phenotypes. Secondly, we examined how polygenic risk scores (PRS) of eight traits that showed heterogeneous correlation patterns with OCD, MDD, ADHD, and ASD partitioned across comorbid subgroups in OCD using independent unpublished data from the Lundbeck Foundation Initiative for Integrative Psychiatric Research (iPSYCH). The comorbid subgroups comprised of patients with only OCD (N = 366), OCD and MDD (N = 1052), OCD and ADHD (N = 443), OCD and ASD (N = 388), and OCD with more than 1 comorbidity (N = 429). We found that PRS of all traits but BMI were significantly associated with OCD across all subgroups (neuroticism: p = 1.19x10-32, bipolar disorder: p = 7.51x10-8, anorexia nervosa: p = 3.52x10-20, age at first birth: p = 9.38x10-5, educational attainment: p = 1.56x10-4, OCD: p = 1.87x10-6, insomnia: p = 2.61x10-5, BMI: p = 0.15). For age at first birth, educational attainment, and insomnia PRS estimates significantly differed across comorbid subgroups (p = 2.29x10-4, p = 1.63x10-4, and p = 0.045 respectively). Especially for anorexia nervosa, age at first birth, educational attainment, insomnia, and neuroticism the correlation patterns that emerged from genetic correlation analysis of OCD, MDD, ADHD, and ASD were mirrored in the PRS associations with the respective comorbid OCD groups. Dissecting the polygenic architecture, we found both quantitative and qualitative polygenic heterogeneity across OCD comorbid subgroups.